Conservative Non-intervention Approach for Hemodynamically Significant Patent Ductus Arteriosus in Extremely Preterm Infants - Sung, Se In; Chang, Yun Sil; Ahn, So Yoon; Jo, Heui Seung; Yang, Misun; Park, Won Soon (Frontiers in Pediatrics, 2020)
While persistent patent ductus arteriosus (PDA) in preterm infants has been known to be associated with increased mortality and morbidities including bronchopulmonary dysplasia, and necrotizing enterocolitis, there is minimal evidence supporting their causal relationships, and most traditional medical and/or surgical treatments have failed to show improvements in these outcomes. As such, the pendulum has swung toward the conservative non-intervention approach for the management of persistent PDA during the last decade; however, the benefits and risks of this approach are unclear. In this mini review, we focused on whom, when, and how to apply the conservative non-intervention approach for persistent PDA, especially in extremely preterm infants.